Tidal stress triggering of earthquakes in Southern California. Issue 2 (8th February 2016) - Bucholc, Magda; Steacy, Sandy
Abstract: We analyse the influence of the solid Earth tides and ocean loading on the occurrence time of Southern California earthquakes. For each earthquake, we calculate tidal Coulomb failure stress and stress rate on a fault plane that is assumed to be controlled by the orientation of the adjacent fault. To reduce bias when selecting data for testing the tide-earthquake relationship, we create four earthquake catalogues containing events within 1, 1.5, 2.5 and 5 km of nearest faults. We investigate the difference in seismicity rates at times of positive and negative tidal stresses/stress rates given three different cases. We consider seismicity rates during times of positive versus negative stress and stress rate, as well as 2 and 3 hr surrounding the local tidal stress extremes. We find that tidal influence on earthquake occurrence is found to be statistically non-random only in close proximity to tidal extremes meaning that magnitude of tidal stress plays an important role in tidal triggering. A non-random tidal signal is observed for the reverse events. Along with a significant increase in earthquake rates around tidal Coulomb stress maxima, the strength of tidal correlation is found to be closely related to the amplitude of the peak tidal Coulomb stress ( τ p ). The most effective tidal triggering is found for τ p ≥ 1 kPa, which is much smaller than thresholds suggested for static and dynamic triggering of aftershocks.